KEMAMPUAN PEMECAHAN MASALAH SISWA SMA PADA MATERI APLIKASI MATRIKS - Wanda Anggeraeni Solihin Putri; Astriana Putri (Journal on Education, 2019)
Problem solving ability has the benefit that can train the students such as in comprehensing the problem, planning the solve, problem solving, and construing the solution. The aim of this research is to analyze students’ problem solving abilities in senior high school at XI grades on matrix aplication material. Students’ problem solving abilities through story exercise forem is still low because it’s still many students that can not construe the story exercise into math form. This research used the qualitative descriptive method to analyzed students’ problem solving abilities in solve the story exercise. The result of this research is students that can not construe the story exercise into math form is can not solve the problem which is given, and the students can construe the story exercise into math form is can solve the problem, even though there are some students that can not solve exercise yet by the right solution.